Social climate, pro-social behaviour and school violence as predictors of school inadaptation in Primary School (European Journal of Education and Psychology, 2010)
The general aim of this work is to analyse how students? perception of social climate, pro-social behaviour and the observation and experience of school violence contribute to predict their social and emotional adaptation reported by parents and teachers. The study has been conducted on a sample of 88 pupils between 8 to 10 years of age, belonging to a Primary School in the province of Málaga, Spain. The results show that the sample presents low marks in variables associated with poor social adaptation and standard marks in variables related to a successful social adaptation. The correlations between the predicting variables and criterion show two different patterns: meanwhile parents? data are more actively associated to social climate and the experience of violence, teachers? data are to pro-sociality and the experience of violence. The regression analysis also offers two different patterns for parents and teachers, stressing the influence of experienced daily school violence upon the results of social and educational adaptation and the importance of pro-social behaviour to predict good academic results of students in Primary School.